2017
DOI: 10.1016/j.bjhh.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Ib open label, randomized, safety study of SANGUINATE™ in patients with sickle cell anemia

Abstract: BackgroundTreatment of sickle cell anemia is a challenging task and despite the well understood genetic and biochemical pathway of sickle hemoglobin, current therapy continues to be limited to the symptomatic treatment of pain, supplemental oxygen, antibiotics, red blood cell transfusions and hydroxyurea. SANGUINATE is a carbon monoxide releasing molecule and oxygen transfer agent under clinical development for the treatment of sickle cell anemia and comorbidities.MethodsAn open-label randomized Phase Ib study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 13 publications
0
33
0
Order By: Relevance
“…In a human study (Phase I), SANGUINATE™ was found to be safe and well tolerated in healthy volunteers, and its half-life was dose dependent and ranged from 7.9 h to 13.8 h [82]. Interestingly, the half-life of SANGUINATE™ at a dose of 160 mg Hb/kg was prolonged in stable sickle cell anemia patients (about 20 h) compared to that in healthy volunteers (13.8 h) [83]. Although two cases where patients received SANGUINATE™ under emergency conditions were reported [78], large scale clinical trials in patients will be needed prior to clinical applications.…”
Section: Newer Generated Acellular Type Hbocsmentioning
confidence: 99%
“…In a human study (Phase I), SANGUINATE™ was found to be safe and well tolerated in healthy volunteers, and its half-life was dose dependent and ranged from 7.9 h to 13.8 h [82]. Interestingly, the half-life of SANGUINATE™ at a dose of 160 mg Hb/kg was prolonged in stable sickle cell anemia patients (about 20 h) compared to that in healthy volunteers (13.8 h) [83]. Although two cases where patients received SANGUINATE™ under emergency conditions were reported [78], large scale clinical trials in patients will be needed prior to clinical applications.…”
Section: Newer Generated Acellular Type Hbocsmentioning
confidence: 99%
“…Our study is the first to evaluate an alternative to PRBC with a potential to ameliorate the burden of sensitization. SG has been studied and demonstrated to be safe and well tolerated in healthy volunteers (dose up to 160 mg/kg) and stable sickle cell disease patients (dose up to 320 mg/kg) . In both studies, there was an expected transient increase in the blood pressure due to SG.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusion criteria included (i) blood product transfusion within 90 days from screening; (ii) ECG findings or symptoms suggestive of acute coronary syndrome, decompensated heart failure, third degree AV block or cardiac arrhythmias associated with hemodynamic instability; (iii) echocardiographic estimate of tricuspid regurgitant jet velocity of ≥2.8 m/s (based on data associating SG with pulmonary hypertension in stable sickle cell disease patients); (iv) severe or unstable cardiovascular, hemato‐oncologic, or neuropsychiatric illness; (v) elevated bilirubin (total bilirubin > 1.5 mg/dL) or transaminitis (ALT/AST >2 times the upper limit of normal); (vi) treatment with an investigational drug or immunosuppressive medications including corticosteroids within 90 days from screening; (vii) alcohol and/or illicit drug use and/or abuse; (viii) AIDS or seropositivity for HIV, hepatitis B surface antigen, hepatitis B core antibody, or hepatitis C antibody within a year from screening; (ix) innate or acquired immunodeficiency other than that associated with uremia; (x) uncontrolled diabetes mellitus (HbA1c > 9%); and (xi) any other condition that, in the opinion of the principal investigator, renders a patient unable to participate in the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations